Evaluation of benefits of optimum sowing time on yield and economics of spring sunflower under frontline demonstrations: Evaluation of benefits of optimum sowing time on yield and economics of spring sunflower under frontline demonstrations - O P LATHWAL,; P S MALIK, (Journal of Oilseeds Research, 2014)
A total of 76 frontline demonstrations were conducted to evaluate the effect of sowing time on productivity and economics of spring sunflower at farmers' fields during the years 2008 to 2012 in Kurukshetra district, Haryana. The crop sown in first fortnight of February produced 11.3 and 34.8% more seed yield than the crop sown in second fortnight of February and first fortnight of March, respectively on an average basis of five years study. Sowing the seed in second fortnight of February also recorded 21.1% higher yield over March sowing. Fluctuating price of produce could not compensate the consistently increased cost of cultivation (8.7-11.0% hike every year) during the years 2008 to 2012. Early sowing in first fortnight of February gave 20.3 and 73.9% more net returns than the crop sown in second fortnight of February and first fortnight of March, respectively. Sowing the crop in second fortnight of February also enhanced the net returns by 44.5% over the sowing in first fortnight of March.